Positron emission tomography–computed tomography-associated incidental neoplasms of the thyroid gland - K Kamakshi; Arvind Krishnamurthy; V Karthik; Preetha Vinodkumar; R Kumar; K Lakshmipathy (World Journal of Nuclear Medicine)
With the increasing use of 18F-fluorodeoxyglucose (FDG) positron emission tomography–computed tomography (PET-CT) scans in oncology, the finding of thyroid incidentalomas, also popularly described as PET-associated incidental neoplasms (PAINs) of the thyroid gland is not unusual. The 18F-FDG PET-CT scans of all patients who underwent imaging for indications other than thyroid malignancy at our tertiary care center between January 1 and December 31, 2017, were retrospectively reviewed for PAINs of the thyroid. A total of 173718F-FDG PET-CT scans were done at our center in the year 2017. 288 thyroid incidentalomas were detected in the said period; the rate of PET-CT-detected thyroid incidentalomas being 16.58%, focal incidentalomas among them being 11.7%. Only 29 out of 204 patients (14.21%) with focal thyroid incidentalomas in our cohort underwent an aspiration cytology and/or ultrasound. The rate of malignancy among the PET detected focal thyroid incidentalomas in the cohort of patients with a proven diagnosis was 10.34%. Our study highlights the challenges in the evaluation and management of PAIN in a tertiary care oncology setting. None of the factors studied including nodule size and standardized uptake value predicted the risk of malignancy. Clinicians specializing in the management of thyroid nodules need to understand the clinical significance of the PAIN, and we hope that our unique experience adds to the limited clinical information available in this regard.